2017
DOI: 10.1371/journal.pone.0175204
|View full text |Cite
|
Sign up to set email alerts
|

Association between serum prolactin levels and insulin resistance in non-diabetic men

Abstract: Prolactin (PRL) has roles in various physiological functions. Although experimental studies showed that PRL has both beneficial and adverse effects on type 2 diabetes mellitus, clinical findings in subjects with hyperprolactinemia indicate adverse effects on glucose metabolism. However, effects of PRL within the physiological range in human are controversial. A population-based study of 370 Japanese men enrolled in the 2014 Iwaki study (aged 52.0 ± 14.8 years). In this cross-sectional study, associations betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 39 publications
2
42
2
Order By: Relevance
“…In fact, several recent prospective studies suggested that the associations between prolactin and risk of type 2 diabetes and the metabolic syndrome were more likely to be beneficial in women but tended to be null or even detrimental in men [1721]. The reason underlying this sex difference is unclear, as both beneficial and detrimental effects of prolactin on IR have been reported in men [12, 44]. Nevertheless, our data, coupled with prior evidence, suggest that prolactin may be related to pathogenic pathways leading to the development of type 2 diabetes in women.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, several recent prospective studies suggested that the associations between prolactin and risk of type 2 diabetes and the metabolic syndrome were more likely to be beneficial in women but tended to be null or even detrimental in men [1721]. The reason underlying this sex difference is unclear, as both beneficial and detrimental effects of prolactin on IR have been reported in men [12, 44]. Nevertheless, our data, coupled with prior evidence, suggest that prolactin may be related to pathogenic pathways leading to the development of type 2 diabetes in women.…”
Section: Discussionmentioning
confidence: 99%
“…This study was part of the Iwaki Health Promotion Project, an ongoing community-based health promotion study of Japanese people over 20 years of age with the aim of preventing lifestyle-related diseases and prolonging lifespans. [18][19][20][21] The study has been conducted annually since 2005 in the Iwaki area of the city of Hirosaki in Aomori Prefecture, northern Japan. All subjects volunteered to participate in response to a public announcement, and approximately 600 items of data from each participant, including body mass index, medical histories (hypertension, diabetes mellitus, and dyslipidemia), and blood pressure, were recorded.…”
Section: Methodsmentioning
confidence: 99%
“…This study was part of the Iwaki Health Promotion Project, which is an ongoing community-based health promotion study of Japanese people over 20 years of age that aims to prevent lifestylerelated diseases and prolong lifespans. [15][16][17] The study has been conducted annually since 2005 in the Iwaki area of the city of Hirosaki in Aomori Prefecture, which is located in northern Japan. All study subjects participated voluntarily in response to a public announcement and approximately 600 items were collected from each participant, including a standard 12-lead ECG, body weight, medical history, cardiovascular risk factors, and blood chemical analysis results.…”
Section: Study Populationmentioning
confidence: 99%